Endwall aerodynamic losses from turbine components within gas turbine engines - Phil Ligrani; Geoffrey Potts; Arshia Fatemi (Propulsion and Power Research, 2017)
A survey of research on aerodynamic loss investigations for turbine components of gas turbine engines is presented. Experimental and numerically predicted results are presented from investigations undertaken over the past 65 plus years. Of particular interest are losses from the development of secondary flows from airfoil/endwall interactions. The most important of the airfoil/endwall secondary flows are passage vortices, counter vortices, and corner vortices. The structure and development of these secondary flows are described as they affect aerodynamic performance within and downstream of turbine passage flows in compressible, high speed flows with either subsonic or transonic Mach number distributions, as well as within low-speed, incompressible flows. Also discussed are methods of endwall contouring, and its consequences in regard to airfoil/endwall secondary flows.